1997
DOI: 10.1097/00005053-199704000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Processing in Borderline Personality Disorders

Abstract: The aim of this study was to examine the ways in which adults with borderline personality disorder (BPD) experience and manage their feelings. Responses of 30 subjects who met the criteria for BPD on the Structured Clinical Interview for DSM-III-R were compared with 40 non-BPD controls on the following measures of emotion processing and affect regulation: 1) level of emotional awareness, 2) capacity to coordinate mixed valence feelings, 3) accuracy at identifying facial expressions of emotion, and 4) intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
188
6
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(217 citation statements)
references
References 24 publications
21
188
6
2
Order By: Relevance
“…In the first published study, Levine and coworkers presented expressions of basic emotions from the "Pictures of Facial Affect" (Eckman & Friesen, 1976) and found that borderline patients were less accurate in terms of emotion recognition, especially for expressions of anger, disgust, and fear (Levine, Marziali, & Hood, 1997). This result was replicated and extended by Bland, Williams, Scharer, and Manning (2004), who found in their study that recognition accuracy was impaired for fearful, angry, and sad faces.…”
Section: Facial Emotion Recognition In Bpdmentioning
confidence: 99%
“…In the first published study, Levine and coworkers presented expressions of basic emotions from the "Pictures of Facial Affect" (Eckman & Friesen, 1976) and found that borderline patients were less accurate in terms of emotion recognition, especially for expressions of anger, disgust, and fear (Levine, Marziali, & Hood, 1997). This result was replicated and extended by Bland, Williams, Scharer, and Manning (2004), who found in their study that recognition accuracy was impaired for fearful, angry, and sad faces.…”
Section: Facial Emotion Recognition In Bpdmentioning
confidence: 99%
“…First, descriptive studies consistently show that compared with psychiatric and non-psychiatric control participants, DSH patients (often diagnosed with borderline personality disorder) score signifi cantly higher on self-report measures tapping emotion regulation diffi culties, including lower emotional awareness and clarity (Leible & Snell, 2004;Levine, Marziali,…”
mentioning
confidence: 99%
“…Here again, the literature provides contradictory results: good EFE perception was found in one study (Wagner & Linehan, 1999) and accuracy problems in another (Levine, Marziali, & Hood, 1997). These discrepancies might be due to a difficulty to isolate borderline patients without co-morbidities like depression or substance abuse.…”
Section: Borderline Personality Disordermentioning
confidence: 95%